The effect of training, work ability and organizational commitment on performance of uptd employees pondok high public health center - Wazirman Wazirman; Letmiadi Letmiadi; Alsabri Alsabri; Riki Apriyono; Adi Kusuma Jaya (Journal of Educational and Learning Studies, 2021)
This study aims to see the effect of (1) Training on the Performance of UPTD Public Health Center Pondok Tinggi Employees (2) Work Ability on Employee Performance UPTD Pondok Tinggi Public Health Center (3) Organizational Commitment to Employee Performance UPTD Pondok Tinggi Health Center (4) Training, Work Ability and Organizational Commitment have a joint effect on the Employee Performance of Sungai Liuk Community Health Center, Pesisir Bukit District.Population and samples in this research whole There are 70 employees of the Pondok Tinggi Health Center UPTD. The results of this study indicate that (1)Training has a positive significant effect on the performance of UPTD Public Health Center Pondok Tinggi employees (2) Work ability provide a positive influence on the performance of UPTD Public Health Center Pondok Tinggi employees (3) Organizational Commitment has a negative influence on the performance of UPTD Public Health Center Pondok Tinggi employees (4) Training, Employability and Organizational Commitment jointly have a positive effect on the employee performance of Sungai Liuk Community Health Center, Pesisir Bukit District.